Hypoxia mediates immune escape of pancreatic cancer cells by affecting miR-1275/AXIN2 in natural killer cells - Ou, Zhenglin; Lu, Yebin; Xu, Dayong; Luo, Zhen (Frontiers in Immunology, 2023)
Given the increasing incidence of pancreatic cancer and the low survival rate, the exploration of the complex tumor microenvironment and the development of novel treatment options is urgent. NK cells, known for their cytotoxic abilities and modulation of other immune cells, are vital in recognizing and killing cancer cells. However, hypoxic conditions in the tumor microenvironment have been found to impair NK cell functionality and contribute to tumor immune escape. Therefore, we aimed to uncover the mechanism through which hypoxia mediates the immune escape of pancreatic cancer cells, focusing on the influence of miR-1275/AXIN2 on NK cells. Using a combination of GEO dataset screening, Tumor Immune Estimation Resource 2.0 immunoscore screening, and the Cancer Genome Atlas data, we identified a correlation between miR-1275 and NK cells. The down-regulation of miR-1275 was associated with decreased NK cell activity and survival in patients with pancreatic cancer. Pathway analysis further linked miR-1275 expression with the hypoxic HIF1A pathway. In vitro experiments were conducted using the NK-92 cell, revealing that hypoxia significantly reduced miR-1275 expression and correspondingly decreased the cell-killing ability of NK cells. Upregulation of miR-1275 increased perforin, IFN-γ and TNF-α expression levels and enhanced NK cell cytotoxicity. Additionally, miR-1275 was found to bind to and inhibit AXIN2 expression, which when overexpressed, partially alleviated the promotive effect of upregulated miR-1275 on NK-92 cell killing ability. In conclusion, this research underscores the critical role of the miR-1275/AXIN2 axis in hypoxia-mediated immune escape in pancreatic cancer, thus opening new potential avenues for treatment strategies.